Safety profile of the adjuvanted recombinant zoster vaccine: Pooled analysis of two large randomised phase 3 trials. Issue 18 (24th April 2019) - ,; Ahonen, Anitta; Avelino-Silva, Thiago Junquera; Barba-Gomez, Jose Fernando; Berglund, Johan; Cuixart, Carlos Brotons; Caso, Covadonga; Chlibek, Roman; Choi, Won Suk; Cunningham, Anthony L.; Desole, Maria Guiseppina; Eizenberg, Peter; et al.
Highlights: These data provide a comprehensive overview of the safety profile of RZV from two pivotal phase 3 studies. A favourable benefit-risk profile of RZV was demonstrated. This overview will help healthcare practitioners in making informed clinical decisions. Abstract: Background: The ZOE-50 (NCT01165177) and ZOE-70 (NCT01165229) phase 3 clinical trials showed that the adjuvanted recombinant zoster vaccine (RZV) was ≥90% efficacious in preventing herpes zoster in adults. Here we present a comprehensive overview of the safety data from these studies. Methods: Adults aged ≥50 (ZOE-50) and ≥70 (ZOE-70) years were randomly vaccinated with RZV or placebo. Safety analyses were performed on the pooled total vaccinated cohort, consisting of participants receiving at least one dose of RZV or placebo. Solicited and unsolicited adverse events (AEs) were collected for 7 and 30 days after each vaccination, respectively. Serious AEs (SAEs) were collected from the first vaccination until 12 months post-last dose. Fatal AEs, vaccination-related SAEs, and potential immune-mediated diseases (pIMDs) were collected during the entire study period. Results: Safety was evaluated in 14, 645 RZV and 14, 660 placebo recipients. More RZV than placebo recipients reported unsolicited AEs (50.5% versus 32.0%); the difference was driven by transient injection site and solicited systemic reactions that were generally seen in the first week post-vaccination. The occurrence of overall SAEs (RZV: 10.1%; Placebo: 10.4%), fatal AEs (RZV: 4.3%; Placebo: 4.6%), and pIMDs (RZV: 1.2%; Placebo: 1.4%) was balanced between groups. The occurrence of possible exacerbations of pIMDs was rare and similar between groups. Overall, except for the expected local and systemic symptoms, the safety results were comparable between the RZV and Placebo groups irrespective of participant age, gender, or race. Conclusions: No safety concerns arose, supporting the favorable benefit-risk profile of RZV.